Efficacy, reactogenicity, and safety of the adjuvanted recombinant zoster vaccine for the prevention of herpes zoster in Chinese adults ≥ 50 years: A randomized, placebo-controlled trial - Diana Alexandra Echeverria Proano; Fengcai Zhu; Xiaodong Sun; Jesús Zoco; Jyoti Soni; Neeraj Parmar; S. Omar Ali (Taylor & Francis Group, 2024)
Phase III multi-country studies (ZOE-50/70) demonstrated that the adjuvanted recombinant zoster vaccine (RZV) was well tolerated and prevented herpes zoster (HZ) in healthy ≥ 50-year-olds, with a vaccine efficacy (VE) > 90% across age groups. These pivotal trials did not enroll participants from mainland China where RZV is licensed, therefore similar clinical data are missing for this population. In this phase IV observer-blind study (NCT04869982) conducted between 2021 and 2023 in China, immunocompetent and medically stable ≥ 50-year-olds were randomized 1:1 to receive two RZV or placebo doses, 2 months apart. This study assessed the VE (overall, as confirmatory objective, and descriptively by age category [50-69-year-olds/≥ 70-year-olds]), reactogenicity, and safety of RZV in this Chinese population. Of the 6138 enrolled participants, 99.2% completed the study. During a mean follow-up period of 15.2 (±1.1) months, 31 HZ episodes were confirmed (RZV = 0; placebo = 31) for an incidence rate of 0.0 vs 8.2 per 1000 person-years and an overall VE of 100% (89.82-100). The descriptive VE was 100% (85.29-100) for 50-69-year-olds and 100% (60.90-100) for ≥ 70-year-olds. Solicited adverse events (AEs) were more frequent in the RZV vs the placebo group (median duration: 1-3 days for both groups). Pain and fatigue were the most frequent local and general AEs (RZV: 72.1% and 43.4%; placebo: 9.2% and 5.3%). The frequencies of unsolicited AEs, serious AEs, potential immune-mediated diseases, and deaths were similar between both groups. RZV is well tolerated and efficacious in preventing HZ in Chinese ≥ 50-year-olds, consistent with efficacy studies including worldwide populations with similar age and medical characteristics.